What Kind of Technology Devices Can be Used to Improve Agronursing Practice?: A Scoping Review - Munawaroh, Lailiyatul (Journal of Rural Community Nursing Practice, 2025)
Background: Agronursing plays an important role in improving health services in rural area. Currently, health services in rural area face various challenges. Technology devices can help nurse to provide community-based health services in this area. This article aims to explore the existing literature related to the use of technology in nursing practice to answer three main questions: (1) what technology devices are commonly used to provide community-based health services, (2) what are the advantages and disadvantages of each devices (3) what are the benefits of these devices in agnonursing practice. Methods: The author conducted an article search using three databases, namely science direct, pubmed, and proquest using “Technology Device AND Nursing Practice” and “Robotic Device AND Nursing Practice” as the keywords. The inclusion criteria for the articles were (1) research articles from Randomized controlled trial and quasi experiment, (2) published between 2020-2025, (3) Published in English while the exclusion criteria was research conducted in hospital setting. Results: The author analyzed 28 articles that met the inclusion and exclusion criteria. The Author found that commonly used devices are monitoring system, robotic devices, mobile app, virtual reality, artificial intelligence, and web-based health intervention. However, these devices have their own advantages and disadvantages that can be considered when applying them in agronursing practice. Conclusions: Digital health technologies can enhance nursing services in agrarian communities. Tailoring these tools to rural needs is vital. Further research is needed to compare which type of device is most effective and efficient in improving agronursing practice.